Old Vilnius in the Perspektive of Nations’ Historical Consciousness - Bumblauskas, Alfredas (Lietuvos istorijos studijos, 2000)
The article deals with the newest historiography on the analyses of Vilnius history through the use of multiperspective methodology (Multiperspektivität). The history of Vilnius (14th-16th c.) due to its multiethnic, multicultural, and multiconfessional aspects suits this methodological reflection since it does not seek to find "objective" monoview or to equalise the relief of historical identities but, on the contrary, to discover concepts and subjects which can reveal the variety of historical consciousness or even help in their formation. Theses - capital of Lithuania, Vilnius is a multiethnic and multicultural city, is banal and does not need to be proved. Although there is no such insight in the current historiography. On the one hand, the status of Vilnius as a capital was argued because of its multiethnicity; on the other hand, the question of multiculture was often neglected by stressing Polish, Russian, or Byelorussian heritage and thus participating in the political partition of Vilnius. The main tendencies of the different development of historical perspectives. Nowadays, changes in the model of cultural history of Lithuania could be found: from baltophilical (S. Daukantas) and lithuanocentric (A. Šapoka) concepts towards the concept of Lithuania’s Europeanisation formulated by E. Gudavičius and research of J. Bardach signifying the independence of Lithuania at the end of the 18th century. We also could discuss new preconditions for the perspectives of historical consciousness of Lithuanian Poles (for example: introduction of the Polish-speaking nobility into the 19th-century Lithuanian society, theory of Europeanisation). These premises allow us to form insights on the perspective of Lithuanian Poles’ historical consciousness. The reality of Lithuanian Russians’ and Ukrainians’ historical consciousness forms an insight that correct scientific historiographical bases have to be developed for the research on identities of the ethnic groups mentioned above. The phenomenon of the Vilnius Jewish community brings Lithuanian capital into another higher trajectory of historical consciousness. Vilnius could be called "Northern Jerusalem" not only because of its phenomenal role in Jewish culture but also because it is very difficult to find so many nations and confessions living so close to each other as here at the end of the 20th century. In this context, Lithuanian capital appears as a sphere of gravitation and junction of several civilizations and also as the coexistence space of several confessions.